Structural and Magnetic Properties of Dimeric and Tetrameric Copper (II) Complexes with Simple Bidentate Ligands and Phosphate Bridges - Sureshbabu P.; Upadhyay C.; Sabiah S. (My University, 2025)
Monomeric [Cu(DACH)(L)]2+ (DACH=1,2-diaminocyclohexane) heteroleptic copper(II) complexes (1–4) on reaction with diphenyl phosphate yielded dinuclear phosphate bridged copper(II) complexes [Cu2L2(dpp)3]+ (5–7), [dpp=diphenyl phosphate; L=bpy (5), Phen (6), 5, 6 dimethyl phenanthroline, (7)] and a tetra-nuclear [Cu4(2,9-dmp)2(dpp)4(OH)2]2+ complex (8) (2, 9 dmp=2, 9 dimethyl phenanthroline). Interestingly, isomeric ligands 5,6-dmp and 2,9-dmp yielded dinuclear complex 7 and tetra-nuclear complex 8 triggered by steric effects. Even though the initial combination contains mixed bidentate ligands, the resulting complexes have only one type of bidentate ligand around the copper(II) ions. These reactions involve ligand expulsion to form the phosphate bridged complexes. All the phosphate bridged complexes 5–8 were characterized by elemental analysis, absorption spectrum, FT-IR, ESI-MS, and single-crystal XRD. The molecular structures show Cu(II) in square pyramidal/trigonal bipyramidal geometry with phosphate in μ-1,3-bridging mode. All complexes exhibit intra-antiferromagnetic interactions with negative J values from variable temperature magnetic susceptibility study by SQUID measurements. © 2022 Wiley-VCH GmbH.